An Interactive Web Application For Administering Indonesian Thesaurus - Az-Zahra, Aulia Afifah Nur; , Husni Thamrin, M.T, P.h.D (2015)
An interactive website is an internet page that uses various codes to create an interactive experience that allows a person viewing the web page to be actively engaged with the site. An interactive web site consists of two parts, i.e. the client browser and the server-side system. The client browser contains components that are directly accessed by the user, while the server-side system contains data and application that manage them at the computer server. This writing describes the result of a final project that creates an interactive web application to display dictionary and thesaurus in bahasa Indonesia, and administering the knowledge base. Administrative tasks include the addition, modification and deletion of Indonesian phrases, phrase definitions, phrase relationshisp and synsets. The focus of this application is to speed up the task of administration. The application employs JQuery so that a user may use drag and drop mode to annotate relationship of phrases and definitions during the creation of synsets. 46 students from Department of Bahasa Indonesia has tested the application and they suggest that in general this application is work so good. From the questionnaire knows that application can helpful and simply in adding new phrase, updating the phrase and so on.